The dural angioleiomyoma harbors frequent GJA4 mutation and a distinct DNA methylation profile - Tauziède-Espariat, Arnault; Pierre, Thibaut; Wassef, Michel; Castel, David; Riant, Florence; Grill, Jacques; Roux, Alexandre; Pallud, Johan; Dezamis, Edouard; Bresson, Damien; Benichi, Sandro; Blauwblomme, Thomas; et al. (Acta Neuropathologica Communications, 2022)
The International Society for the Study of Vascular Anomalies (ISSVA) has defined four vascular lesions in the central nervous system (CNS): arteriovenous malformations, cavernous angiomas (also known as cerebral cavernous malformations), venous malformations, and telangiectasias. From a retrospective central radiological and histopathological review of 202 CNS vascular lesions, we identified three cases of unclassified vascular lesions. Interestingly, they shared the same radiological and histopathological features evoking the cavernous subtype of angioleiomyomas described in the soft tissue. We grouped them together with four additional similar cases from our clinicopathological network and performed combined molecular analyses. In addition, cases were compared with a cohort of 5 soft tissue angioleiomyomas. Three out 6 CNS lesions presented the same p.Gly41Cys GJA4 mutation recently reported in hepatic hemangiomas and cutaneous venous malformations and found in 4/5 soft tissue angioleiomyomas of our cohort with available data. Most DNA methylation profiles were not classifiable using the CNS brain tumor (version 12.5), and sarcoma (version 12.2) classifiers. However, using unsupervised t-SNE analysis and hierarchical clustering analysis, 5 of the 6 lesions grouped together and formed a distinct epigenetic group, separated from the clusters of soft tissue angioleiomyomas, other vascular tumors, inflammatory myofibroblastic tumors and meningiomas. Our extensive literature review identified several cases similar to these lesions, with a wide variety of denominations. Based on radiological and histomolecular findings, we suggest the new terminology of “dural angioleiomyomas” (DALM) to designate these lesions characterized by a distinct DNA methylation pattern and frequent GJA4 mutations.
Der Ausdruck "GJA4" ist kursiv dargestellt
Gesehen am 11.07.2022